. The significance of serum sST2 and cfDNA in children with severe pneumonia complicated by myocardial damage: serum sST2 and cfDNA in children with severe pneumonia complicated by myocardial damage - Zhao, Tingting (Journal of Medical Biochemistry, 2024)
Objective: The paper aimed to explore the significance of serum sST2 and cfDNA to prevent atrial inflammation in children with severe pneumonia complicated by myocardial damage. Methods: 120 children with severe pneumonia complicated by myocardial damage who were treated in the Children's Department of the author's hospital from April 2021 to December 2023 were recruited as research subjects. The children were randomly divided into two groups, one group of 60 children received personalized care intervention based on serum sST2 and cfDNA (personalized care group), and the other group of 60 children received routine care (routine care group). The clinical data of the two groups of patients were compared. The changes in serum sST2 and cfDNA levels of patients were compared before and after care. ELISA kits were used to test atrial inflammation marker levels before and after patient care. The patient's cardiac function was assessed through cardiac ultrasound. the nursing intervention effects of the two groups was compared. The patient satisfaction with nursing care was compared between the two groups. Results: There was no distinction in the general record of the two groups (P>0.05). Before care, there was no distinction in serum sST2 and cfDNA levels between the two groups (P>0.05). After care, the serum sST2 and cfDNA levels in the personalized care group were lower than those in the routine care group (P0.05). After nursing, the levels of CRP, cTn, 1L-6 and TNF-α in personalized nursing were lower than those in the conventional nursing group (P
Keywords: sST2; cfDNA; severe pneumonia complicated by myocardial damage; atrial inflammation